Change in Cochlear Response in an Animal Model of Otitis Media with Effusion - Dai, Chenkai (S. Karger AG, 2010)
Our previous studies confirm that middle ear mobility is reduced in the presence of otitis media with effusion (OME). Variations in middle ear function may result in changes in cochlear response in OME ears. With the long-term goal of evaluating cochlear function in OME ears, the aim of this study was to measure the displacement of the basilar membrane (BM) in guinea pig ears with OME. Vibrations of the BM at the apex and basal turn were measured in an in vitro preparation extracted 3 and 14 days after injection of lipopolysaccharide in the middle ear of guinea pigs. The results show that the displacement sensitivity of the BM at the apex and the basal turn to sound pressure in the ear canal was reduced up to 25 dB at their characteristic frequencies, respectively. Cochlear gain with respect to umbo movement was also changed in ears with OME in both groups. This study provides data for analysis of the change of BM vibration in a guinea pig OME model.